Financial Strategy and Competitiveness of Merger in Malaysian Islamic Banking industry - Zainal Abidin, Azlan (2015)
Islamic banking in Malaysia has come a long way since its humble beginnings in 1983 when the Islamic Banking Act was first introduced. In the same year, the first fully Sharia compliant Islamic bank namely Bank Islam Malaysia was established to give a much needed boost to the Islamic finance industry to cater to the Muslim majority population of Malaysia. The Asian Financial Crisis in 1997 and the subsequent Global Financial Crisis of 2008 have each given the world a glimpse of the need to merge financial institutions as well as the advantages of Islamic financing. Malaysia’s Islamic banks and/financial institutions are currently ranked 3rd in terms of Sharia compliant assets size behind Iran and Saudi Arabia; which has raised the question of the need of a Mega Islamic bank to cater to the market as Islamic banking has become more and more appealing to both Muslims and non-Muslims in Malaysia for its profit sharing concept. As Islam is also currently the fastest growing religion in the world, many would seek Islamic banking and/or financing to cater to their everyday lives as it is in the Islamic teachings that interest or riba is haram (not permissible). This is recorded in the Holy Book of Quran, in Surah Al-Baqarah verse 275 which states:- “Those who devour Riba will not stand (especially for judgement before Allah) except as stands one whom Satan by his touch has driven to madness. That is because they argue: “Business and Riba are similar to each other.” But Allah has made “business” Halal and He has made ‘Riba’ Haram. Those who after receiving this warning (concerning the Haram of Riba) from their Lord, (now) desist (from Riba), may keep whatever they had previously earned (as Riba); and their case (will now be judged by) Allah (alone ,i.e. the Islamic State will not deal with that matter); but those who return (to Riba even after this revelation of the Quran ) are companion of fire (of Hell) ; they abide therein (forever).”